Lung Volume Abnormalities and its Correlation to Spirometric and Demographic Variables in Adult Asthma. (August 2013) - Jain, Vipul V.; Abejie, Belayneh; Bashir, Muhammad H.; Tyner, Tim; Vempilly, Joseph
Abstract : Background. Presence of airflow obstruction in asthma has been based on a fixed FEV1(forced expiratory volume at 1 second)/FVC (forced vital capacity) ratio abnormality. The accuracy of FEV1/FVC ratio in diagnosing airflow obstruction remains controversial. Lung volume abnormalities have been observed in severe asthma. We utilized simultaneously measured spirometry and lung volume to determine the utility of residual volume (RV)/total lung capacity (TLC) ratio in diagnosing airflow obstruction and to identify predictors of abnormal RV in asthmatic subjects. Methods . Data from physician-diagnosed asthmatics referred for lung function tests were collected retrospectively. Patient demographics and lung function data were analyzed using general linear modeling. Results. Of the 321 subjects, 221 were female (69%). The ethnicity was Caucasian in 157 (49%), Hispanic in 131 (41%), and African-American in 33 (10%). The percentage of subjects with FEV1/FVC ratio <70%, FEV1-predicted <80%, and FEF25–75% <65% were 25%, 25%, and 38%, respectively. Fifty-two and fifty-seven percent of the patients had abnormal residual volume and abnormal RV/TLC ratio, respectively. A significant bronchodilator response was observed in 32% of the patients. A positive correlation was observed between RV to age ( r = 0.4) and height ( r = 0.3). A negative correlation was observed between RV to FEF25–75% ( r = 0.5) and body weight ( r = 0.07). There was no significant correlation between FEV1 reversibility and residual volume ( r = 0.1). RV correlated significantly better with FEF25–75% ( r 2 = 0.25) than FEV1 ( r 2 = 0.16). Conclusion . A significant proportion of asthmatic patients have elevated residual volume and abnormal RV/TLC ratio in the presence of normal FEV1/FVC ratio and absence of significant bronchodilator response. The clinical significance of these findings in asthma needs further prospective study.